DAMPAK PERUBAHAN TARIF PPH UMKM TERHADAP KEPATUHAN PERPAJAKAN DAN PENERIMAAN PAJAK DI KOTA TANGERANG - Shierly Sephiani; Syafitri, Wildan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
One type of potential tax is income tax. Indonesia has many MSMEs and contributes to 61.97% of national GDP. However, the contribution of MSMEs to the tax sector is not comparable to the tax revenue. The lack of awareness among MSME taxpayers is one of factors for the low level of tax compliance, which has a domino effect on the amount of tax revenue. The Government’s regulation as a response to the problem is through the implementation of PP 23/2018. The Government reduced tax rate from 1% to 0.5% would to make it easier for MSMEs and increase tax compliance. The domino effect will strengthen the role of MSMEs as a biggest source for the Indonesian economy, including increasing tax revenue. The research was conducted in Tangerang City to describe how far the effect of changes in PPh rates has on MSME taxpayer compliance and tax revenue in a city with the title of “Kota Seribu Industri”. The method used is quantitative descriptive analysis. The results of this study that the reduction in tariffs increases the number of taxpayers, which also has implications for increasing tax compliance. But on the contrary, the realization of tax revenue actually decreased.